Studying the reliability of evaluating the force reproduction error of elbow extensor muscles in healthy young men - Elaheh Amini; Minoo Khalkhali Zavieh; Asghar Reza Soltani; Alireza Akbarzadeh Baghban (Vesnu Publications, 2013)
Abstract Introduction: The proprioception is good protector of joints against movement injuries and saves joint stability and is their natural co-ordinator during movement. As the force sense reproduction  is one of the common methods for evaluating the proprioception,its reliability must be evaluated .So the objective of this study is surveing the reliability of evaluating the force reproduction error of dominant and non dominant elbow extensor muscles in healthy young men . Methods & materials: in this study ,12 healthy young men between 18-30 years old which were selected by simple convenient non probability sampling from students of rehabilitation faculty of  Shahid Beheshti university of medical sciences in 1391 were recruited .The intratester and intertester reliability was astudied  .For analizing the sense of force reproduction error in elbow extensor muscles using forcemeter ,we instructed the specified percent (30%) of maximal isometric contraction to the subjects and then asked them to reproduce the instructed force. After two minutes we asked the subjects to repeatedly reproduce the instructed force.The test was repeated 3 times in each  order .The error of sense of force was computed using the difference of target force and reproducted force during three repetitions in first and second orders .The study was repeated randomly in dominat and non dominant limbs .Relative reliability (ICC) ,absolute reliability (SEM) and comparing the measures of two repetitions by paired t-test used for studying the reliability. Results: the amounts of ICC for constant error ,absolute error and variable error in dominant(right) limb and non dominant (left) limb were from 0.76 to 0.94 which shows high reliability.The SEM measures were from 0.004 to 0.02. Conclusion: based  on  the results of this sudy ,it was concluded that the method of evaluating the error of  sense of force in both limbs of healthy young men has high reliability .So it can be used as a reliable method in evaluating the force reproduction error. Keywords : proprioception, reliability, force  reproduction error, elbow.